Kepemimpinan Rohani Guru PAUD Kristen di Era Disrupsi : Studi Pustaka Model Adaptif untuk Membentuk Karakter Kristiani Anak Berdasarkan Teladan Kristus - Yosfhina Limbong Lembung; Herlina Siska; Melianti Toding Allo; Elisabet Nirta; Yurnita Sampe Bassang (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The disruption era, marked by rapid technological development and socio-cultural transformation, presents significant challenges to the spiritual and character formation of young children. In this dynamic context, Christian Early Childhood Education (ECE) teachers are not merely facilitators of learning but are also expected to act as spiritual leaders and moral role models. These responsibilities require a form of leadership that is not only rooted in biblical principles but also adaptive to the shifting demands of the digital age. This study aims to (1) identify the core challenges faced by Christian ECE teachers in the disruption era, (2) examine Christ-centered leadership values, and (3) propose an adaptive spiritual leadership model suitable for Christian ECE settings. Utilizing a qualitative approach through a literature review, data were analyzed using Miles and Huberman’s interactive model, which includes data condensation, data display, and conclusion drawing. The findings highlight two main categories of challenges: external challenges such as the influence of digital media, shifting values in society, and increased parental expectations; and internal challenges including limited teacher capacity, spiritual stagnation, and institutional gaps. In response, this research proposes the "Three-Pillar Adaptive Spiritual Leadership Model," which emphasizes: (1) the teacher's internal spiritual formation and integrity, (2) the implementation of innovative and contextually relevant pedagogical strategies grounded in Christian values, and (3) synergistic collaboration with families and church communities as key support systems. This model provides a conceptual and practical framework for Christian educational institutions to empower teachers in forming resilient, Christ-like character in children. The study contributes to the discourse on faith-based education in the 21st